Competitive Strategy, Performance Appraisal and Firm Results - Alberto Bayo-Moriones; Jose Enrique Galdon-Sanchez; Sara Martinez-de-Morentin (Institute for the Study of Labor (IZA), 2016)
In this study, we address the relationship between performance appraisal and competitive strategy, as well as the impact of this relationship on firm performance. The results indicate that the adoption of developmental performance appraisal and the use of administrative performance appraisal are higher among firms that pursue differentiation strategies compared to those competing on costs. Regarding firm performance, the interaction between a developmental appraisal system and a quality strategy displays higher return on equity and sales per employee. Those firms that combine a focus on innovation with administrative performance appraisal also enjoy higher performance. Finally, when the firm competes on the basis of cost reduction, the use of administrative appraisal increases the sales per employee.
Keywords: M12; M52; 330; performance appraisal; competitive strategy; firm performance; developmental appraisal; administrative appraisal